1993
DOI: 10.1029/92jd02161
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of atmospheric hydroxyl radical concentrations from the observed decay of many reactive hydrocarbons in well‐defined urban plumes

Abstract: An analytical system has been developed which allows the confident identification and measurement of 35 hydrocarbons of different reactivities in air samples collected in many locations. This paper describes the application of the technique to follow the differential decay of hydrocarbons in urban plumes spreading from London during the summer. The data have been used to determine atmospheric hydroxyl radical concentrations, averaged over several hours, on the assumption that the decay of the hydrocarbons is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 13 publications
3
56
0
Order By: Relevance
“…Thus, the explanation of the observed high values of benzene in the area during nighttime seems to be complicated. Toluene (see Figure 6) hourly values showed that the maximum values were recorded in the morning hours (7)(8) and the minimum values during afternoon hours (17-18 LT), a behavior similar to that of benzene and NO 2 , certifying that the three pollutants have the same origin. It is obvious that toluene exhibits a larger and sharper diurnal variation than that of benzene.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the explanation of the observed high values of benzene in the area during nighttime seems to be complicated. Toluene (see Figure 6) hourly values showed that the maximum values were recorded in the morning hours (7)(8) and the minimum values during afternoon hours (17-18 LT), a behavior similar to that of benzene and NO 2 , certifying that the three pollutants have the same origin. It is obvious that toluene exhibits a larger and sharper diurnal variation than that of benzene.…”
Section: Resultsmentioning
confidence: 94%
“…The specific ratios of BTX could be changed because of photochemical reactions caused by different lifetimes of the aromatics. Aromatics have been measured in some European cities in recent years, specifically in Milan, 6,7 London, 8 and Munich, 9 while Moschonas and Glavas 10 and Rappenglueck et al 11 measured aromatics in Athens using mainly the gas chromatograph (GC) (in situ or flask sampling) technique. The differential optical absorption spectrometer (DOAS) technique was recently used in Goteborg, 12 Rome, 13 and Thessaloniki.…”
Section: Introductionmentioning
confidence: 99%
“…This would indicate that the source mixtures are similar in urban centres in the two countries. The York distribution is less similar to the distributions seen in Sydney, Australia or London, England (Blake et al, 1993). The latter two profiles appear enriched in acetylene and olefins, species known to be reactive on vehicle catalytic convertors.…”
Section: Hydrocarbon Distributionsmentioning
confidence: 81%
“…This concept of using reactive tracers to determine the OH concentration has been discussed (and improved) in several publications in the past, like e.g. : Singh et al (1981); Roberts et al (1984); McKeen et al (1990);Satsumabayashi et al (1992); Blake et al (1993);McKenna et al (1995); Kramp and Volz-Thomas (1997). Other studies use the ratio of NO 2 to NO y to determine the photochemical age (Kleinman et al, 2008;Slowik et al, 2011).…”
Section: P Barmet Et Al: Oh Clock Determination By Proton Transfer mentioning
confidence: 99%